1999
DOI: 10.1128/jvi.73.8.6680-6690.1999
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Chemokine Receptor Fusion Cofactor Utilization by Human Immunodeficiency Virus Type 1 Variants from the Lungs and Blood

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection is highly compartmentalized, with distinct viral genotypes being found in the lungs, brain, and other organs compared with blood. CCR5 and CXCR4 are the principal HIV-1 coreceptors, and a number of other molecules support entry in vitro but their roles in vivo are uncertain. To address the relationship between tissue compartmentalization and the selective use of entry coreceptors, we generated functionalenv clones from primary isolates derived from the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 63 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Coreceptor-dependent, Env-mediated fusion is assessed on the basis of transactivation of a reporter gene due to cell content mixing [11,12], although Env overexpression in effector cells may lead to differences from Env expressed in the context of virions. In particular, cell-cell fusion assays may overestimate coreceptor utilization when compared with infection, for example, many minor coreceptors that support HIV-1 cell-cell fusion assays are less active or even inactive in the context of virus infection [63,64].…”
Section: Target Cells To Define Coreceptor Usementioning
confidence: 99%
“…Coreceptor-dependent, Env-mediated fusion is assessed on the basis of transactivation of a reporter gene due to cell content mixing [11,12], although Env overexpression in effector cells may lead to differences from Env expressed in the context of virions. In particular, cell-cell fusion assays may overestimate coreceptor utilization when compared with infection, for example, many minor coreceptors that support HIV-1 cell-cell fusion assays are less active or even inactive in the context of virus infection [63,64].…”
Section: Target Cells To Define Coreceptor Usementioning
confidence: 99%
“…It is mapped at 2q33.3 and encodes for a G proteincoupled receptor for the inflammation-associated leukocyte chemoattractant chemerin/RARRES2 [retinoic acid receptor responder (tazarotene induced) 2] considered as an adipokine in children 106 , as well as for a putative membrane-bound G protein, associated in the activation of cAMP synthesis 107 . GPR1 protein"s role as a coreceptor for HIV-1 is supported by the literature [108][109][110] . The GPR1 G protein-coupled receptor suggests an association with respiratory distress syndrome (RDS).…”
Section: Resultsmentioning
confidence: 79%
“…Because both NSI and SI variants were detected in different tissues, the existence of tissue reservoirs apart from the brain was discounted, and the presence of HIV in nonlymphoid tissues was seen as a late-stage event secondary to lymphocyte infiltration (168). By using functional env clones from primary isolates, Singh's group (151) examined the HIV co-receptor utilization patterns in the lung and showed that the lung isolates used CCR5 as exclusive co-receptor, while the blood isolates may use either CCR5 or CXCR4. Furthermore, lung and blood isolates were undistinguishable regarding the use of secondary co-receptors, including CCR2b, CCR3, CCR8, and CX3CR1 and orphan receptors GPR1, GPR15, and STRL33, suggesting that co-receptor utilization does not determine HIV compartmentalization in the lung, despite the biological differences between HIV quasispecies in the blood and the lung.…”
Section: Hiv Reservoirsmentioning
confidence: 99%